PERCEPTION OF SECURITY AND PROTECTIVE STRATEGIES: DIFFERENCES BETWEEN PERSONALITY PROTOTYPES - Anna Rebecca Mueller; Mandy Roeder (European Scientific Journal, ESJ, 2014)
The present study investigates the relation between personality traits and perceptions of security as well as the relation between personality traits and protective strategies of university students. For that reason, 295 university students were asked about their general perceptions of security, specific worries, and used or desired protective strategies as well as their personality via questionnaire. With a cluster analysis, three personality types could be identified (resilient, overcontrolled, undercontrolled). Those personality types differ with regard to their perception of security at night, their fear of sexual assaults, and their use of several protective strategies. Hence, personality traits are not only associated with different levels of perception of security but also with the use of protective strategies.